Profile of Underdiagnosis Lung Cancer with Pulmonary Tuberculosis at Arifin Achmad General Hospital, Pekanbaru - Munir, Sri Melati; Aulia, Ananda Febriani; Simatupang, Elvando Tunggul Mauliate; Tanlie, Veghasanah (Indonesian Journal of Cancer, 2025)
Background: Lung cancer and pulmonary tuberculosis are respiratory issues that collectively account for the world’s leading cause of mortality. Indonesia, being a nation endemic for Pulmonary Tuberculosis, frequently encounters instances of diagnosis overlap with lung cancer. Delays in the diagnosis of both pulmonary tuberculosis and lung cancer have a global impact on morbidity and mortality. Based on this, this study aims to determine the profile of Lung Cancer patients who were previously diagnosed as pulmonary tuberculosis as an initial diagnosis that can provide new criteria in establishing a diagnosis between pulmonary tuberculosis and lung cancer.Method: This study is a descriptive cross-sectional study using total sampling collected over 1 year. The inclusion criteria were lung cancer patients previously diagnosed with clinical pulmonary tuberculosis, with or without anti-tuberculosis drugs obtained from medical record data. All results are presented in the form of a distribution table. Results: Twenty seven patients diagnosed with adenocarcinoma, with the highest prevalence among males (77.78%). The duration of delay was less than 6 months (62.96%), being the highest rate in this study. Due to the delay in diagnosis, all patients diagnosed with lung cancer were at stage IV. Discussion: Adenocarcinoma is the most common form of lung cancer in men and individuals over 40 years old. Lung cancer with a latency duration of 6 months is typically diagnosed at stage IV. Clinical pulmonary tuberculosis must be investigated further if no clinical improvement is observed after one month of anti-tuberculosis drug treatment.Conclusion: Diagnostic delays of lung cancer significantly impact patient survival. Screening for suspected lung cancer in clinical pulmonary tuberculosis is crucial to reduce morbidity and mortality. Sputum cytology and low-dose CT scan may be utilized as screening modalities.